S88. THE EFFECT OF SLEEP QUALITY ON ATTENUATED PSYCHOTIC SYMPTOMS IN A NON-CLINICAL SAMPLE OF YOUNG ADULTS. (18th May 2020) - Hanna, Donncha; James Shannon, Ciaran; Clarke, Stephen; Davidson, Sarah; Mulholland, Ciaran
Abstract: Background: Background: One factor known to be associated with attenuated psychotic symptoms is poor sleep but it is not known if poor sleep increases the likelihood of experiencing multiple attenuated psychotic symptoms, which research suggests may be suggestive of an At-Risk Mental State (ARMS). The study aimed to determine if poor sleep quality makes a unique contribution to predicting the number of attenuated psychotic symptoms endorsed in a prodromal questionnaire and the level of distress associated with the symptoms, when accounting for demographics, depression and drug/alcohol use variables. Methods: Method: An online survey was conducted using Amazon's online crowdsourcing service Mechanical Turk (MTurk). The sample was 1, 013 adults (18 to 36 years) from the general population in the USA. The survey consisted of the Prodromal Questionnaire 16 (PQ-16), the Pittsburgh Sleep Quality Index, the Patient Health Questionnaire 9 (PHQ-9), the DAST-10 and the AUDIT. Regression analyses were performed with the PQ-16 as the dependent variable, and sleep quality as the predictor variable, while controlling for sociodemographic variables, depression, and alcohol/drug abuse. Results: Results: 37% of the sample endorsed six or more PQ-16 items, which may be suggestive of an at-risk mental state, with sleep disturbance significantly increasing the likelihood (Odds ratio 2.09 <.001) of endorsing six or more PQ-16 items. After controlling for socio-demographic variables, depression and drug/alcohol abuse, poor sleep quality made a unique contribution of 5.8% of the variance accounted for in level of distress experienced by attenuated psychotic symptoms. Discussion: Conclusion: A significant proportion of young adults in the general population may have an at-risk mental state. The results add to the evidence that sleep disturbance is a contributory factor in attenuated psychotic symptoms. Further research is required to investigate the possible mechanisms (e.g. impaired cognitive processes) through which poor sleep influences attenuated psychotic symptoms and if effective treatment of sleep disturbance can influence the likelihood of developing an at-risk mental state.